Operation of BaSi2 homojunction solar cells on p+-Si(111) substrates and the effect of structure parameters on their performance. (19th March 2019) - Kodama, Komomo; Yamashita, Yudai; Toko, Kaoru; Suemasu, Takashi
Abstract: Operation of n + -BaSi2 /p-BaSi2 (500 nm)/p + -BaSi2 homojunction solar cells on p + -Si(111) is demonstrated, showing a saturation current density of 9.4 mA cm −2 and an open-circuit voltage of 0.11 V under AM1.5 illumination. Photogenerated electrons deep in the p-BaSi2 light absorber layer are likely to be transferred to the p + -Si side, leading to negative values of internal quantum efficiency ( IQE ) at longer wavelengths. The negative IQE can be solved by extending the width of depletion region in the p-BaSi2 light absorber layer by decreasing its hole concentration. The importance of Si substrate surface morphology is also discussed.